'A Network of Trust': Measuring and Monitoring Air Pollution in British Cities, 1912-1960. (1st August 2009) - Mosley, Stephen
Abstract : This paper examines the origins and development of the first nationwide air pollution monitoring network of its kind. The Investigation of Atmospheric Pollution was founded in 1912 with less than 30 participating bodies. By the 1960s it had expanded its research activities to involve over 500 cooperating authorities and organisations in almost every major British town and city. The paper is set out in three interrelated parts. Firstly, it explores how central and local government, representatives of industry, and non-governmental organisations worked together to establish an expert body that could gather information on polluted air, despite their different interests and agendas. Secondly, it draws historical attention to the importance (and difficulties) of technical standard-setting in providing reliable and policy-relevant knowledge about environmental pollution. Lastly, it will examine the uses of monitoring in efforts to raise public awareness of the problems caused by coal smoke and its role in supporting action to reduce urban air pollution, particularly after the 1952 London smog disaster.